Cytological sampling at fibreoptic bronchoscopy: comparison of catheter aspirates and brush biopsies. Issue 6 (June 1982) - Muers, M F; Boddington, M M; Cole, M; Murphy, D; Spriggs, A I
Abstract : A prospective study was undertaken to compare bronchial brushings with dry catheter aspiration for the cytological diagnosis of lung cancer at fibreoptic bronchoscopy. Duplicate samples taken by aspirate and brush were obtained at 103 consecutive routine bronchoscopies. Aspirate and brush samples were reported on separately by two cytologists. At the end of the study a 30% sample, including the 19 cases with different findings by the two methods, were subjected to a blind crossover review, and then an open review. Forceps biopsy specimens for routine histological assessment were taken in 94 cases (92%). Ninety-eight of 103 (95%) aspirates and 99 of 103 (96%) brush specimens were technically satisfactory. Carcinoma was diagnosed at bronchoscopy on cytological or histological evidence or both in 57 cases. Fifty-five of these tumours (96%) were recognised by either the aspirate or the brush method, 52 (91%) by brush, and 50 (88%) by aspirate. Thirty-four cases (60%) could be diagnosed from histological specimens. The order of cytological sampling did not systematically affect yield. It is concluded that fine-catheter aspirates, permitting smears to be prepared in the laboratory, are a satisfactory alternative to brush smears for the cytological diagnosis of lung cancer at bronchoscopy. The routine use of both techniques at bronchoscopy will increase diagnostic yield by about 5%. Duplicate sampling may be especially useful in obtaining diagnostic material from upper-lobe or apical-segment tumours.